National survey on the presence of multidisciplinary meetings for interstitial lung diseases (ILD-MDM) in hospitals in Germany - Bauer, Claus-Juergen; Skowasch, Dirk; Kreuter, Michael; Hamer, Okka W.; Behr, Jürgen; Gläser, Sven; Heußel, Claus Peter; Kütting, Daniel; Krause, Andreas; Leuschner, Gabriela; Markart, Philipp; Petzinna, Simon Michael; et al. (Zeitschrift für Rheumatologie, 2025)
Interstitial lung diseases (ILD) represent an interdisciplinary clinical challenge and are not uncommonly associated with rheumatological diseases. Interstitial lung disease multidisciplinary meetings (ILD-MDM) provide a structured platform for interdisciplinary case discussions and decision making. Despite their great importance in patient care, data on the prevalence, structure and function of ILD-MDM in Germany are lacking.
Gesehen am 02.02.2026